HUBUNGAN ANTARA PENGETAHUAN AKSEPTOR KB SUNTIK DENGAN KETEPATAN WAKTU SUNTIK KB DI BPS KHANIFAH, KABUPATEN TANGERANG, PROPINSI BANTEN PERIODE JANUARI – DESEMBER 2017 - Krisdiana, Riffany; So, Ernawati (Fakultas Kedokteran Universitas Tarumanagara, 2021)
According to World Population Data Sheet 2013, Indonesia is the fifth country in the world with the largest population estimate. Therefore, the problem of resident can be overcome one of them with KB (Family Planning), because KB is a way to regulate the number of children. The most common type of contraception is hormonal contraception because it works effectively, is relatively inexpensive, safe, simple, effective and can be used postpartum. There are 3 hormonal contraceptives that are pills, injections and implants. Currently, injectable contraception has the best effectiveness, provided the injection is regular and appropriate as the time schedule of the injection. The accuracy of re-injecting is an acceptance of the acceptors' compliance. If inaccurate injection will reduce the effectiveness of contraception such as injectable contraceptive failure. Factors that affect the accuracy of time injection is the attitude, behavior and knowledge acceptors about KB. Therefore failure factor of injectable contraception method can be caused by acceptor delay in doing re-injection. The purpose of this research is to know the correlation between knowledge of KB contraceptive acceptor with the accuracy of reinjection time. It is a correlational research, cross sectional approach, research sample of all mothers who become KB contraceptive acceptor in BPS Khanifah and meet inclusion criteria. Technique of sampling consecutive non random sampling with randomly taken as many as 58 people. Data were analyzed with Chi-Square. The results showed most respondents are knowledgeable and timely as much as 18 (31.0%) while not on time as much as 10 (17.2%). Statistically there was a significant correlation between knowledge with accuracy of injecting contraceptive acceptor (p = 0,032) and PR value 1.48.